Optimization problems arising in emerging cellular network technologies - Ooh, Yi Jie. (2012)
This report makes use of optimization to find out the optimal location of a fixed number of DAS antennas in order to provide coverage to the maximum number of users in a cell which contains an additional femtocell. Firstly, literature review is done to find out how a cellular network operates. Research is done mainly concentrating on DAS antenna system as well as the CDMA process. Next, research is done to find out what is a femtocell, how it works, as well as the benefits and disadvantages of using a femtocell. Next, a mathematical model is used to find out the objective function. The mathematical model consists of different constraint equations as well as the objective function, which is to maximize the number of users within the cell. A particular project scenario is used in the course of this report. This scenario assumes that 2 DAS antenna locations out of 4 possible locations would be chosen to provide coverage. Besides that, a base station located at the origin as well as a femtocell would also provide coverage to the cell. After that, two distinct scenarios are used to find out the optimized location of the DAS antenna. In the first scenario, 75 users would be projected to be within the cell. In the second scenario, 100 users would be projected to be within the cell.